Rapid Electrochemical Detection of Pseudomonas aeruginosa Signaling Molecules by Boron-Doped Diamond Electrode - Buzid, A.; Luong, J.; Reen, F.; O'Gara, Fergal; Glennon, J.; McGlacken, G. (Humana Press, 2018)
As the leading cause of morbidity and mortality of cystic fibrosis (CF) patients, early detection of Pseudomonas aeruginosa (PA) is critical in the clinical management of this pathogen. Herein, we describe rapid and sensitive electroanalytical methods using differential pulse voltammetry (DPV) at a boron-doped diamond (BDD) electrode for the detection of PA signaling biomolecules. Monitoring the production of key signaling molecules in bacterial cultures of P. aeruginosa PA14 over 8 h is described, involving sample pretreatment by liquid-liquid and solid-phase extraction. In addition, direct electrochemical detection approach of PA signaling molecules is also reported in conjunction with hexadecyltrimethylammonium bromide (CTAB) to disrupt the bacterial membrane.